LA CONSOLIDACIÓN DE LA OFICINA MUNICIPAL DE LA MUJER. EL CASO DE HEREDIA - González Espinoza, Meyling (Universidad de Costa Rica, 2016)
The article presents the experience of management policies and actions to promote genderequality and equity in the area of the Municipality of Heredia. It’s analyzed the strategicmanagement process that shows the complementation with global and national developmentsin this topic at the municipal level. It’s a guide to the work of promoting in an areawhere these policies and actions required interventions and practices of excellence for theirpoor development in the country.